(untitled) (Journal of Economic Research & Business Administration, 2015)
Success of macroeconomic reforms implemented to date in Kazakhstan, created favorable conditions for a shift of focus on regional development policy as an important and promising tool to improve the overall level of socialeconomic development of the country whose potential still has not been used to the full. Thus, according to this message, President NursultanNazarbayev to the people of Kazakhstan (March, 2006), as a result of the search for new tools for development of non-primary sectors, more adapted to the conditions prevailing in Kazakhstan, with an emphasis on regional development appeared social-entrepreneurial corporations (SEC). Socio-entrepreneurial corporationsvirtuallyrelegated to the roleof the basic mechanismto ensurea breakthrougheconomic and socialdevelopment of the country, until the occurrenceof the 30 mostdeveloped countriesof the world